NUMERICAL MODEL AND SIMULATION OF FLUID WITH NON-UNIFORM DENSITY - Rizki Amartya, Geniung
Fluid flow with density differences is a natural phenomenon that often occurs in this world. Some examples are the phenomenon of Fraser River plume and the Kelvin-Helmholtz cloud formation. In this final project, the author will study the behavior of fluid flow with non-uniform density by constructing a governing equation model from the Euler equation. The fluid is assumed incompressible and non-viscous. The model that has been built is discretized using the finite numerical method on the Arakawa C-grid and solved by the successive over relaxation (SOR) method. A numerical scheme was implemented to simulate non-uniform density fluids, such as with horizontal density differences, vertical density differences, and Fraser River Delta topography. The numerical result is compared with Bernoulli's theory, Kelvin-Helmholtz instability theory, and video experiments. The comparisons show quite good results. The numerical scheme can simulate the turbulence that arises so that it induces the process of mixing fluids with non-uniform density. The numerical scheme can also simulate the formation of a Kelvin-Helmholtz wave and the formation of a mixing zone which corresponds to the mixing zone value of the Kelvin-Helmholtz instability.